Avaliação da potencialidade de incorporação de um lodo de uma indústria de produtos de limpeza como adição mineral em concretos de cimento Portland - Silva, José Daniel Jales (2015)
The generation of industrial wastes has been increased more and more in recent decades, motivating studies about a correct sustainable allocation and that also represents advantages for their generators. In this context, are included two companies of cleaning products niche, located in São José do Mipibu/RN, that produces industrial sludge at a sewage treatment plant, and that is the main approach of this research. Given this, it was studied the incorporation potentiality of this sludge as a mineral addition in cement matrix for concrete production due it high capacity of wastes immobilization inside this material, which are subsequently used in the company for making precast articles. Were added different sludge concentrations (5, 10, 15 and 20%) in a common trait (1: 2: 3), and evaluated their techniques and microstructural implications via workability test in fresh state and compressive strength, full porosity and scanning electron microscopy (SEM) in the hardened state. The results demonstrated the feasibility of the process both from a technical and environmental view as economical. All concretes produced with residue showed an increase of workability given the nature of the waste that had surfactants substances capable of adsorbing tiny particles of air into the batter. However, for all concentrations were obtained lower compressive resistances than standard concrete, with a reduction of 39% for samples with 20% of sludge. This are attributed mainly to an increase of porosity in the transition zone of these material, resulting from increased formation of ettringite at the detriment to the formation of other compounds, but which still allows the use of these for the manufacture of concrete articles with non-structural nature, such as precast floor. In addition, the water absorption and void ratio increased slightly for all samples, except the concrete with 20% of waste that has a reduction for the last parameter. Given this context, the recommended maximum level is 20%, constituting a significant proportion and able to allocate sustainably all waste generated in the industry.